Late-Holocene vegetation dynamics in response to a changing climate and anthropogenic influences – Insights from stratigraphic records and subfossil trees from southeast Lithuania. (1st April 2018) - Edvardsson, Johannes; Stančikaitė, Miglė; Miras, Yannick; Corona, Christophe; Gryguc, Gražyna; Gedminienė, Laura; Mažeika, Jonas; Stoffel, Markus
Abstract: To increase our understanding of long-term climate dynamics and its effects on different ecosystems, palaeoclimatic and long-term botanical reconstructions need to be improved, in particular in underutilized geographical regions. In this study, vegetation, (hydro)climate, and land-use changes were documented at two southeast Lithuanian peatland complexes – Čepkeliai and Rieznyčia – for the Late-Holocene period. The documentation was based on a combination of pollen, plant macrofossils, peat stratigraphic records, and subfossil trees. Our results cover the last two millennia and reveal the existence of moist conditions in Southern Lithuania between 300 and 500 CE and from 950 to 1850 CE. Conversely, changes towards warmer and/or dryer conditions have been recorded in 100, 600, and 750 CE, and since the 1850s. Significant differences with other Baltic proxies prevent deriving a complete and precise long-term reconstruction of past hydroclimatic variability at the regional scale. Yet, our results provide an important cornerstone for an improved understanding of regional climate change, i.e. in a region for which only (i) few detailed palaeobotanical studies exist and which has, in addition, been considered as (ii) an ecologically sensitive region at the interface between the temperate and boreal bioclimatic zones. Highlights: Our multiproxy approach yields detailed data on vegetation and climate dynamics in southeast Lithuania. Moist/cold periods in southeast Lithuania were recorded 300–500 and 950–1850 CE. Warmer and/or dryer conditions were recorded 100, 600, 750 CE, and since the 1850s. The use of climatic proxies of similar resolution and covering the last 2k yrs is rare in this ecologically sensitive area.